2011
DOI: 10.1016/j.ultrasmedbio.2011.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian Parameter Estimation for Characterizing the Cyclic Variation of Echocardiographic Backscatter to Assess the Hearts of Asymptomatic Type 2 Diabetes Mellitus Subjects

Abstract: Previous studies have shown that effective quantification of the cyclic variation of myocardial ultrasonic backscatter over the heart cycle might provide a non-invasive technique for identifying the early onset of cardiac abnormalities. These studies have demonstrated the potential for measurements of the magnitude and time delay of cyclic variation for identifying early onset of disease. The goal of this study was to extend this approach by extracting additional parameters characterizing the cyclic variation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…More recent application of these studies has been to characterize diabetes [8081]. In one study, comparisons between normal subjects and patients with type 2 diabetes demonstrated that parameterization of the ultrasonic backscatter from the myocardium could differentiate between the hearts of diabetic patients based on their diabetic control.…”
Section: Successful Applications Of Quantitative Ultrasoundmentioning
confidence: 99%
“…More recent application of these studies has been to characterize diabetes [8081]. In one study, comparisons between normal subjects and patients with type 2 diabetes demonstrated that parameterization of the ultrasonic backscatter from the myocardium could differentiate between the hearts of diabetic patients based on their diabetic control.…”
Section: Successful Applications Of Quantitative Ultrasoundmentioning
confidence: 99%
“…(Many "ultrasound" uses of Bayesian methods in the literature are really more generic post-processing or image processing algorithms (e.g. [4])). The reason for this is not clear, but in some cases it may be the lack of an appropriate, practical likelihood function.…”
Section: Introductionmentioning
confidence: 99%